1984
DOI: 10.3168/jds.s0022-0302(84)81425-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Phenolic Acids and Xylose Content of Cell Wall with In Vitro Dry Matter Digestibility of Three Maturing Grasses

Abstract: Maturing reed canarygrass, Russian wildrye, and smooth bromegrass cell walls were analyzed for lignin, phenolic acids, and neutral sugars. Linear correlation between in vitro dry matter digestibility and the p-coumaric acid content was -.86.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 15 publications
8
34
0
1
Order By: Relevance
“…Digestibility has been shown to decrease as xylose content increases in maturing cool-season grasses. 33 Arabinose concentrations, which were approximately one-tenth of xylose, tended to be higher in the blade, midrib and sheath for lax leaf inbreds compared with public inbreds (data not shown). Although xylose concentration was consistently lower and uronic acid concentration was consistently higher in lax leaf inbred tissues, multiple regression of digestibility on cell wall composition traits indicated that neither xylose nor uronic acid concentrations improved the model's ability to predict digestibility.…”
Section: Results and Discussion Experimentsmentioning
confidence: 99%
“…Digestibility has been shown to decrease as xylose content increases in maturing cool-season grasses. 33 Arabinose concentrations, which were approximately one-tenth of xylose, tended to be higher in the blade, midrib and sheath for lax leaf inbreds compared with public inbreds (data not shown). Although xylose concentration was consistently lower and uronic acid concentration was consistently higher in lax leaf inbred tissues, multiple regression of digestibility on cell wall composition traits indicated that neither xylose nor uronic acid concentrations improved the model's ability to predict digestibility.…”
Section: Results and Discussion Experimentsmentioning
confidence: 99%
“…These 2 acids could therefore cross-link lignin and hemicellulose (Morrison, 1974;Burritt et al, 1984;Scalbert et al, 1985;Jung, 1989;liyama et al, 1990;Kondo et al, 1990). For instance, Helm and Ralph (1991) (1973) found that the bm1 stalks were poorer in AOAC lignin content (sulphuric acid lignin in dry matter).…”
Section: Introductionmentioning
confidence: 99%
“…The major non-core lignin phenolic acids are pcoumaric acid (CA) and ferulic acid (FA). According to Burritt et al (Burritt et al, 1984) and Jung (1989), the ratio of CA to FA present in non-core lignin has a strong negative impact on biomass digestibility. The difference in alkali concentration might be attributed to their pcoumaric to ferulic acids ratio apart from lignin content.…”
Section: Optimization and Validationmentioning
confidence: 99%